2002
DOI: 10.1055/s-2002-35851
|View full text |Cite
|
Sign up to set email alerts
|

Is Endoscopic Ultrasonography Indispensable in Assessing the Appropriateness of Endoscopic Resection for Gastric Cancer?

Abstract: Endoscopic resection is indicated in intramucosal gastric cancer lesions showing differentiated histology, no ulcer fibrosis and a diameter of less than 2 cm. EUS may additionally be used for further evaluation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 7 publications
8
75
0
1
Order By: Relevance
“…However, even recent studies have reported widely varying diagnostic accuracies of 67-90 % when determining the depth of invasion using EUS, making it difficult to view the method as sufficiently reliable [9][10][11][12][13][14]. Furthermore, its diagnostic ability is similar to that of CE alone [15][16][17], and a number of studies have stated that EUS is unsuitable as a routine investigation for determining the depth of invasion by EGCs [15]. In recent years, there have been some promising reports regarding the determination of invasion depth using new modalities such as infrared endoscopy [18] and magnifying endoscopy with narrow-band imaging [19], but these are yet to produce consistently reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…However, even recent studies have reported widely varying diagnostic accuracies of 67-90 % when determining the depth of invasion using EUS, making it difficult to view the method as sufficiently reliable [9][10][11][12][13][14]. Furthermore, its diagnostic ability is similar to that of CE alone [15][16][17], and a number of studies have stated that EUS is unsuitable as a routine investigation for determining the depth of invasion by EGCs [15]. In recent years, there have been some promising reports regarding the determination of invasion depth using new modalities such as infrared endoscopy [18] and magnifying endoscopy with narrow-band imaging [19], but these are yet to produce consistently reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to disease estimation, selection of surgical procedure and prognosis assessment (Willis et al 2000;Kwee and Kwee 2007). With constant improvements in EUS, its superiority in T and N staging of gastric cancer has been demonstrated (Greenberg et al 1994;Hizawa et al 2002;Akashi et al 2006). However, due to the limitation of the probe frequency of endoluminal sonography and the penetration depth of the ultrasonic beam, its inferiority in M staging of gastric cancer (i.e., its incapacity to accurately predict the distant metastasis of gastric cancer) is also shown (Ziegler et al 1993;Bhandari et al 2004;Chen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To date, EUS imaging can be performed with echoendoscopes or with the use of ultrasound catheters or 'miniature probes' which are passed through standard endoscopes. These miniature probes can provide ultra-high-frequency imaging (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), compared to echoendoscopes (5-12 MHz). Higher frequency yields higher resolution of the tumor at the expense of depth of penetration, thus limiting nodal examination [1,2]; thus, a higher frequency probe may provide better evaluation of a T1/T2 cancer, while a lower frequency probe may be more accurate in predicting nodal involvement.…”
Section: Endoscopic Ultrasoundmentioning
confidence: 99%
“…Fifteen studies [7, 17, 19, 20, 22-24, 26, 29-32, 34-36] used combinations of frequencies of B12 MHz and six studies [18,25,27,28,33,37] used combinations of frequencies ranging from 5 to 20 MHz. It was not feasible to construct a 2 9 2 table to investigate transducer frequencies as source of heterogeneity.…”
Section: Eus Examinationmentioning
confidence: 99%